Key paediatric messages from the 2018 European Respiratory Society International Congress - KARADAĞ, BÜLENT TANER (EUROPEAN RESPIRATORY SOC JOURNALS LTD, 2019)
In this article, the Group Chairs and early career members of the European Respiratory Society (ERS) Paediatric Assembly highlight some of the most interesting findings in the field of paediatrics which were presented at the 2018 international ERS Congress.
Keywords: PRIMARY CILIARY DYSKINESIA; BRONCHOPULMONARY DYSPLASIA; PRETERM INFANTS; LUNG-FUNCTION; ASTHMA; DIAGNOSIS; CHILDREN; AZITHROMYCIN; PREVENTION; MUTATIONS